A case study of the different types of squatter resettlement schemes in Kuching city - Woon, Yea Yuan. (2001)
No city in this world is completely free of squatters nor is it realistic to provide housing for every single family that is drawn to its bright lights. Housing policies are facing a challenge when meeting the aims to resettle squatters in urban centres. Different types of squatter resettlement programmes have been implemented to resettle the squatters. This is a comparative study on the different types of squatter resettlement programmes in Kuching city.